Comparison of breastfeeding practice among Iranian and Afghan refugee mothers: a prospective cohort study in Iran - Zohreh Heidary; Mostafa Saeedinia; Haniyeh Fathi; Shima Rafiee; Zohre Khalajinia; Parvaneh Sadeghimoghadam; Mohammadamin Parsaei (Journal of Health, Population and Nutrition)
Abstract Background Breastfeeding is a critical health equalizer and predictor of significant maternal and infant health outcomes, profoundly influenced by the socioeconomic and cultural status of mothers. Previous research has suggested that migration negatively impacts the breastfeeding practices of immigrant mothers. Given that Iran hosts approximately 3 million Afghan refugees, this study aimed to compare the breastfeeding practices of immigrant Afghan mothers in Iran with those of Iranian mothers. Methods This prospective cohort study included postpartum Iranian mothers (n = 209) and Afghan immigrant mothers (n = 327) referred to Nekuei Hedayati Forqani Hospital in Qom and Imam Khomeini Hospital complex in Tehran from January 1, 2023, to May 1, 2023. Breastfeeding quality was assessed using the Bristol Breastfeeding Assessment Tool (BBAT) at baseline (after birth) and at 2-, 4-, and 6-month follow-ups. Breastfeeding continuity was qualitatively assessed based on mothers’ reports of daily frequency and duration of breastfeeding episodes over six months. Results The mean BBAT score of the Iranian cohort was significantly higher than that of Afghan mothers at baseline (7.0 ± 1.5 vs. 6.7 ± 1.7; P-value = 0.032) and at the 6-month follow-up (7.7 ± 0.5 vs. 7.1 ± 1.3; P-value < 0.001), with no significant differences at 2- and 4-month follow-ups (P-values > 0.05). Additionally, the Iranian cohort demonstrated a higher frequency of daily breastfeeding episodes (P-value = 0.001) and longer mean duration per episode compared to the Afghan cohort (P-value < 0.001). Conclusions Our findings suggested that Afghan immigrant mothers tend to have poorer breastfeeding practices than Iranian mothers, which highlights the need for Iran’s healthcare system to offer a multicultural, accessible, educational, and supportive framework to improve these outcomes. Nonetheless, our relatively small sample size, significant sociodemographic disparities between the Iranian and Afghan cohorts, and restriction to urban sampling may limit the generalizability of our results. Future research would benefit from larger, longitudinal studies with nationally representative samples that systematically examine how socioeconomic factors influence breastfeeding practices among Afghan migrant populations in Iran. Trial registration Not applicable.